Cost-effective analysis of sugemalimab plus chemotherapy as first-line treatment for advanced gastric or gastroesophageal junction adenocarcinoma with PD-L1 CPS ≥5 - Zhang, Yalan; He, Ying; Chen, Ruijia; You, Maojin (Frontiers in Public Health, 2025)
BackgroundResults from the GEMSTONE-303 trial indicate that compared with placebo plus capecitabine and oxaliplatin (PLA-CAP), sugemalimab plus capecitabine and oxaliplatin (SUG-CAP) as first-line therapy provides clinical benefits for patients with advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma with programmed cell death ligand 1 (PD-L1) combined positive score (CPS) ≥5. However, the addition of sugemalimab increases medical costs. This study aimed to assess the cost-effectiveness of SUG-CAP vs. PLA-CAP for the first-line treatment of advanced G/GEJ adenocarcinoma with PD-L1 CPS ≥5 from the perspective of China's healthcare system.MethodsA Markov model with three health states was developed to compare the cost-effectiveness of SUG-CAP and PLA-CAP. Clinical data were obtained from the GEMSTONE-303 trial, drug costs were determined based on national bidding prices, and other costs and utility values were obtained from published literature. Outcomes included total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). Sensitivity analysis was used to verify the robustness of the model.ResultsThe SUG-CAP incurred costs of 70,673.28 and gained 1.28 QALYs. In the PLA-CAP, the effectiveness was 1.00 QALYs at a cost of 11,241.52. Compared with PLA-CAP, SUG-CAP yielded an increase of 0.28 QALYs at an incremental cost of 59,431.76. The ICER for SUG-CAP vs. PLA-CAP was 217,686.71 per QALY, which exceeds the preset willingness-to-pay (WTP) threshold of 41,511 per QALY, with a 0% probability of being cost-effective. The parameters that significantly affected the model were the cost of sugemalimab, progression-free survival (PFS) utility, and discount rate.ConclusionFrom the perspective of China's healthcare system, SUG-CAP as first-line therapy for advanced G/GEJ adenocarcinoma with PD-L1 CPS ≥5 is not cost-effective compared with chemotherapy alone.